The ethical and axiological problem of the early Wittgenstein, according to Augusto Salazar Bondy - Trinidad Felipe, Mishell (2023)
This article aims to identify the ethical and axiological problem in early Wittgenstein. This research topic has already been worked by Augusto Salazar Bondy in his book Para una filosofía del valor (2010). We will begin by describing some basic concepts of the Tractatus logico-philosophicus. For example, what is a thing, a state of a thing and a fact. In addition, the concept of the meaning of facts, the function of logic as a principle of figuration and Wittgenstenian transcendentality. For the author of the Tractatus, facts lack any sense other than the sense of being the disposition of things among themselves. Therefore, any other sense that is predicated of facts must reside outside the world. That other sense of facts is ethical statements. On the other hand, according to Wittgenstein, logic is transcendental; since it is not possible to identify it within the world of facts. But ethics is also transcendental, because by means of it we assert moral and aesthetic judgments. These statements are not propositions, since they are neither true nor false. However, such statements affect the subject and the meaning of the facts of the world.